(untitled) (Research, Society and Development, 2021)
The number of new cases of HIV infection has been steadily increasing. In the world scenario, there is an increase in access to antiretroviral therapy and, currently, 26 million people use antiretrovirals. In Brazil, a country that provides full and free access to antiretrovirals, about 630 thousand people are undergoing treatment. This study aims to describe the pharmacokinetic changes of antiretrovirals in patients with different physiological conditions. A bibliographic survey was carried out with studies related to the use of antiretrovirals in specific groups: extremes of age (newborns and elderly), pregnancy, liver diseases, chronic kidney disease, cardiovascular disease, obesity and metabolic disorders, dietary interactions, use and abuse of legal and illegal drugs and genetic polymorphism. In certain situations, changes in pharmacokinetic parameters such as absorption, distribution, metabolism and excretion were observed, as well as variations in plasma levels of antiretrovirals. In the investigated groups, the importance of dose adjustment is highlighted to increase the effectiveness of antiretrovirals, aiming to provide a more adequate treatment to people living with HIV.